Digitale Infrastrukturen für die germanistische Forschung - Lobin, Henning; Schneider, Roman; Witt, Andreas (Germanistische Sprachwissenschaft um 2020, 2018)
Modern research in linguistics is increasingly reliant on digital infrastructure and information systems. This development began at the turn of the millennium and has since accelerated. The volume examines national and European infrastructure networks and the range of language resources in German linguistics that can be discovered, disclosed, and re-applied through digital infrastructure.